Enhancing the Capacity of MSMEs in Digital Marketing at the Modern Creative Industry Institution of Jombang Regency: Peningkatan Kapasitas UMKM dalam bidang Pemasaran Digital pada Lembaga Industri Kreatif Modern Kabupaten Jombang - Fitra, Fitra; Sucipto, Sucipto; Hidayati, Berlina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in economic development, especially in developing countries. However, MSMEs still face challenges in optimally adopting digital technologies and platforms to improve their competitiveness. To overcome this problem, the community service program (PKM) was initiated with a focus on digitizing MSME products. This program involves training and mentoring tailored to the needs and challenges faced by MSMEs, as well as integrating digital marketing concepts and online marketing strategies. The evaluation results showed that the PKM program managed to achieve a high level of satisfaction from participants, with the majority of aspects of the program achieving a high success rate, exceeding 90% for almost all categories. This success shows that the PKM program is effective in increasing the knowledge, skills, and understanding of the partners involved. Furthermore, the existence of grants in the form of technology devices to the Jombang IKM institution to create digital content also shows efforts to support the sustainability of the program and the potential to have a positive impact in increasing product sales.